Black's Law Dictionary - GARNER, Bryan A (West Group, 1999)
Blacks Law Dictionary Digital provides law students and other users with access from their computers to the 43,000 legal definitions found in the Standard 8th Edition of Black s Law Dictionary. Students can instantly find definitions for legal terms from search toolbars that integrate with Microsoft Word, Internet Explorer, and Mozilla Firefox. Black s Law Dictionary Digital also incorporates the correct spellings for all defined terms into the spell check function of Word, ensuring accurate spelling for all legal documents created. Students can even listen to audio pronunciations for thousands of words and phrases, ensuring they never mispronounce another legal term.